Dental Fear and Children: The Major Link - Sonu Acharya1, Susant Mohanty2, Bismay Singh3, Sheetal Acharya4, Jnana Ranjan Swain3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A child’s behavior pattern in any situation is governed by his inherited physical and mental endowment andas he develops,by the conditioning he receives through contact from his environment. The former,exceptwithin normal limits,cannot be altered. The later can be controlled and developed so that the child will growto have a well-adjusted personality to suit the society of which he is a part. Here we discuss how fear governsto a large extent the behavior being shown in a dental operatory by the child and the value of fear.